The Diagnosis of Urinary Tract infection in Young children (DUTY) : a diagnostic prospective observational study to derive and validate a clinical algorithm for the diagnosis of urinary tract infection in children presenting to primary care with an acute illness /: a diagnostic prospective observational study to derive and validate a clinical algorithm for the diagnosis of urinary tract infection in children presenting to primary care with an acute illness. (July 2016) - Hay, A. D (Alastair David)
No abstract available